Penerapan Metode Pembelajaran Kooperatif Numbered Heads Together (NHT) dalam Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Syafura Atika Majidah R Berutu; Ismaraidha Ismaraidha; Hadi Saputra Panggabean (Medan Resource Center, 2026)
Learning of Islamic Religious Education (PAI) in elementary schools often encounters several challenges, including low student participation, teacher-centered learning practices, and suboptimal learning outcomes in cognitive, affective, and psychomotor domains. This study was conducted to analyze the effectiveness of the Numbered Heads Together (NHT) cooperative learning method in improving the quality of the learning process and students’ learning outcomes in PAI subjects. The research employed a qualitative descriptive approach conducted in an elementary school setting. Data were collected through classroom observations, interviews with teachers and students, and documentation studies. The data were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the NHT method was able to create a more interactive, collaborative, and student-centered learning environment. Teachers acted as facilitators who encouraged active student participation during the learning process. The application of the NHT method also contributed to improving students’ understanding of Islamic Religious Education concepts and increasing learning motivation. The percentage of passive students decreased from 65% before implementation to 45% after the application of the NHT method. Therefore, the NHT cooperative learning method can be considered an effective strategy to enhance student engagement and learning outcomes in Islamic Religious Education at the elementary school level.